Methodology for exposure and health risk screening of phthalates potentially present in fabric face coverings. Issue 1 (27th January 2022) - Massarsky, Andrey; Donnell, Melinda T.; Binczewski, Natalie R.; Chan, Kathy; Dinh, Dan; Bare, Jennifer L.; Unice, Kenneth M.
Abstract: To mitigate the spread of COVID-19, face masks, including fabric face coverings, have been encouraged or mandated. To meet demand, traditional clothes-making fabrics have been redirected to face covering manufacture. It has been reported that phthalates may be present in textiles, posing a health risk consideration for the industry; however, the potential presence of and exposure to phthalates in fabric face coverings have not been evaluated. Consequently, this study 1) estimated the concentrations of phthalates in fabric face coverings, 2) estimated the potential consumer exposures, and compared them to health guidance values (HGVs), and 3) advised on voluntary phthalate testing in textiles and/or face coverings. Precautionary upper-bound phthalate mass in face coverings was estimated from phthalate concentrations in clothing articles. Exposure to phthalates was predicted to occur predominantly via inhalation and direct dermal contact; however, for both routes, the doses were below HGVs, indicating that, based on the limited materials characterized in the literature, a health risk was unlikely. Further, the limit of 0.1% (w/w) set for individual or sum of phthalates in child care articles in the U.S. and other countries was deemed protective for children and adult face coverings. We conclude that the establishment of industry-wide voluntary phthalate quality specifications and test data for commercial face coverings or textiles used to manufacture them is advisable to substantiate product safety given the limited data.